Numeric ring-reconstructions based on massifs favor a non-oblique south pole-Aitken-forming impact event - Bernhardt, Hannes; Walsh, Jessica M.; Schröder, Leon M.; Clark, Jaclyn D.; Henriksen, Megan R.; Edwards, Christopher S. (Earth and planetary science letters, 2025)
•Three numeric fits of 201 massifs we identify as likely SPA-ring remnants.•Different fit variants all give outer and inner ellipses with ellipticities ≤ 1.06.•Near-circular SPA would have required impact at non-oblique angle of well over 44°.•≤20% increased impact melt volume, excavation depth, and transient cavity depth.•Expect up to 10 km thick SPA ejecta blanket across Artemis Exploration Zone. The size and shape of ring structures around the South Pole-Aitken basin (SPA) have been subject of several studies over the past decades. Most investigations considered long wavelength signatures such as the topographic outline of the extant basin floor or orbital observations of elemental abundances, all of which are oval or crescent-shaped and therefore implied an elliptic SPA formed by an oblique impact. Here we present a novel dataset of 286 circum-SPA massifs taller than 1000 m prominence, 201 of which we interpret as likely ring remnants based on morphology and location. Using a gradient-based optimization algorithm, we performed three numeric fits of these massifs, each consisting of an outer and an inner ellipse. While one fit included all 201 likely ring remnants, the two other fits included only massifs taller than 2160 m prominence or such that show a negative Bouguer anomaly (like the Outer Rook Ring around Orientale basin). A set of massifs that are part of non-ambiguous, relatively intact SPA-ring segments were given the same weight as all other massifs in every fit. The sizes of our three fits are relatively similar (variances ≤ 3.7%) with semimajor and semiminor axes of the outer ellipses ranging from 1099.4 km to 1126.9 km and 1060.0 km to 1099.4, respectively, and those for the inner ellipses from 946.2 km to 947.4 km and 910.2 to 941.3 km, respectively. As the two more exclusive fits discard massifs that are part of the relatively intact ring segments, we tentatively favor our more inclusive fit using all 201 likely ring remnants, which also has the lowest loss per datapoint value. All our fits have ellipticities ≤ 1.06 resulting in a near-circular SPA, which should have required an impact at a non-oblique angle of well over 44°. Compared to previously assumed lower impact angles around 30° to 45°, 2D and 3D models by previous studies suggest that such a non-oblique SPA-forming impact would increase the volume of generated impact melt, excavation depth, and diameter of the transient cavity, albeit only moderately by up to 20%. The energy injected by the SPA-forming event might be smaller in a non-oblique case because the size of the basin is determined only by the vertical component of the impactor trajectory, allowing for a lower impact energy to explain the diameter of SPA. Most decisively, though, a non-oblique scenario would imply a more symmetric distribution of ejecta, predicting an up to 10 km thick blanket at the South Pole, where oblique scenarios estimated only very small amounts of SPA ejecta. This is in agreement with increased olivine abundances in the regolith at the Chandrayaan 3 landing site and would imply SPA ejecta, including materials from the lower crust and upper mantle, to be relatively widespread in the Artemis Exploration Zone.